Simultaneous determination of phenmedipham, desmedipham, and ethofumesate in a pesticide formulation by normal-phase high-performance liquid chromatography - Velkoska-Markovska, L.; Petanovska-Ilievska, B.; Vodeb, L. (Akademiai Kiado Zrt., 2008)
A normal-phase high-performance liquid-chromatographic method has been developed for simultaneous quantitative analysis of phenmedipham, desmedipham, and ethofumesate in a pesticide formulation. Analysis was performed on a 25 cm × 0.4 cm, 5- μm particle, CN column with n-hexane–dichloromethane 40:60 (v/v) as mobile phase at a flow rate of 1 mL min−1. UV detection was performed at 270 nm; the constant column temperature was 25°C. The run time under these chromatographic conditions was less than 8 min. Calibration plots were linear in the concentration range 76–380 μg mL−1 for phenmedipham, 72–360 μg mL−1 for desmedipham, and 52–260 μg mL−1 for ethofume- sate. Statistical evaluation by analysis of variance showed the intra-day repeatability (n = 8) and inter-day precision (n = 3) of the assay were satisfactory. The sensitivity of the method, as the limits of detection (LOD) and quantification (LOQ) for each active in- gredient, was also determined.